2015
DOI: 10.1111/bjc.12095
|View full text |Cite
|
Sign up to set email alerts
|

Specific, personally meaningful cues can benefit episodic prospection in medial temporal lobe amnesia

Abstract: Previous reports of episodic prospection impairment in medial temporal lobe (MTL) amnesia might misrepresent an individual case's true prospective abilities Specific cues drawn from a patient's everyday life have greater ecological validity than the more typical generic cues used to elicit episodic prospection and can aid some individuals with MTL amnesia in the ability to imagine future experiences Assessment and rehabilitation tools for MTL amnesic populations should attempt to minimize broad, open-ended que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 66 publications
2
20
0
Order By: Relevance
“…Since the cue-word method is one of the most frequently used methods of AM assessment, this suggestion could have implications for future clinical research and the development of sensitive diagnostic approach. In addition, we echo the recent recommendations by Kwan et al (2015), who promoted the overall contribution of these kind of studies in creating more effective ways to structure questions in a personally meaningful way, to interact with people with memory impairment. Whether these findings might be a basis for the development of cognitive interventions aiming to support AM represents an avenue for future research.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Since the cue-word method is one of the most frequently used methods of AM assessment, this suggestion could have implications for future clinical research and the development of sensitive diagnostic approach. In addition, we echo the recent recommendations by Kwan et al (2015), who promoted the overall contribution of these kind of studies in creating more effective ways to structure questions in a personally meaningful way, to interact with people with memory impairment. Whether these findings might be a basis for the development of cognitive interventions aiming to support AM represents an avenue for future research.…”
Section: Discussionsupporting
confidence: 64%
“…In support, such a finding could be related to the self-reference effect, which corresponds to the tendency for people to better remember information relevant to them (see Klein, 2012 for a review). Recently, Kwan, Kurczek, and Rosenbaum (2015) reported similar outcomes in amnesic patients when prompted by personal cues derived from previous past events. Kwan and colleagues suggested that the benefit from personal cues could be related to the activation of some kind of framework conveyed by self-relevant cues, which could then help to structure event details.…”
Section: Discussionmentioning
confidence: 79%
“… ABSTRACT How does the ability to imagine detailed future experiences (i.e., episodic prospection) contribute to choices between immediate and delayed rewards? Individuals with amnesia do not show abnormally steep discounting in intertemporal choice, suggesting that neither medial temporal lobe (MTL) integrity nor episodic prospection is required for the valuation of future rewards (Kwan et al (), Hippocampus, 22:1215‐1219; Kwan et al (2013), J Exp Psychol, 142:1355‐1369 2013). However, hippocampally mediated episodic prospection in healthy adults reduces the discounting of future rewards (Peters and Büchel (2010), Neuron, 66:138‐148; Benoit et al (2011), J Neurosci, 31:6771‐6779), raising the possibility that MTL damage causes more subtle impairments to this form of decision‐making than noted in previous patient studies.…”
mentioning
confidence: 99%
“…For example, Kurczek et al () found that involvement of the hippocampus was more strongly associated with the inclusion of episodic details in future event narratives, whereas involvement of the medial prefrontal cortex (mPFC) was associated with the incorporation of the self in these narratives. In addition, studies with clinical populations have shown that amnesic patients with adult‐acquired medial temporal lobe damage exhibit difficulty imagining personal future events (D'Argembeau et al, ; Hassabis, Kumaran, Vann & Maguire, ; Klein et al, ), and that individuals with frontal lobe damage or deficits exhibit rigidity when generating personal future plans in new environments and from new perspectives (Kwan, Kurczek, & Rosenbaum, ; Unterrainer & Owen, ).…”
Section: Neural Substrates Underlying Episodic Memory and Self‐concepmentioning
confidence: 99%
“…However, it has been suggested that the presence of residual hippocampal tissue in these patients may support intact prospective abilities, and that patients may rely on strategies and semantic knowledge to construct fictitious future events. In fact, some studies have reported that patients who utilize semantic knowledge to construct fictitious future scenes are not able to generate episodic and self‐related details to imagine personal future events (Kwan et al, ; Race, Keane, & Verfaellie, ), suggesting that the types of future events constructed by patients with developmental amnesia may be qualitatively different from those of healthy controls.…”
Section: Neural Substrates Underlying Episodic Memory and Self‐concepmentioning
confidence: 99%